Hiperimunoglobulin E pada Systemic Lupus Erythematosus - yusra, Yusra; Tjahjadi, Ricky (Majalah Kedokteran Indonesia, 2019)
Introduction: Hyperimmunoglobulin E syndrome is a rare multisystem syn-drome which affects musculoskeletal system, connective tissue, and immunesystem. Immune dysregulation in hyperimmunoglobulin E syndrome often ac-companied with autoimmune disease, such as systemic lupus erythematosus.While the role of IgG autoantibody is well known in the pathogenesis of sys-temic lupus erythematosus, other subtypes of autoantibodies, IgE in particu-lar, are now known to be involved in autoimmune process. We describe a caseof adult onset hyperimmunoglobulin E syndrome whom then diagnosed as sys-temic lupus erythematosus on follow-up.